The Joseph story between Egypt and Israel - Römer, Thomas,Schmid, Konrad,Bühler, Axel (online, 2021)
Within the context of the Torah, the Joseph story can be read as a transition that explains why Jacob and his family came to Egypt. However, if one looks at other texts of the Hebrew Bible, there is no mention of the Joseph story; instead, the arrival of the Israelites is said to be the result of the decision of a
20.500.12854/75118
Keywords: Aufsatzsammlung; Religion & beliefs; Criticism & exegesis of sacred texts